HACCP and antibiotic resistance in dairy products: The Armenian experience - Lilit Malkhasyan; Susanna Mirzabekyan; Haykush Batikyan; Astghik Pepoyan (Applied Food Research, 2025)
The spread of antibiotic resistance (AR) in the dairy sector poses a serious threat to food safety, requiring rigorous control strategies. This study aimed to evaluate the effectiveness of the Hazard Analysis and Critical Control Points (HACCP) system in mitigating AR-related risks in dairy products. A total of 70 raw milk samples were randomly collected from supermarkets in Yerevan, Armenia. Antibiotic residues were measured using ELISA-based assays, while 254 bacterial isolates were subjected to antimicrobial susceptibility testing via the Kirby–Bauer disk diffusion method and the automated VITEK® 2 system. Statistical analyses were performed using SPSS software (version 26.0, IBM Corp., USA), with t-tests and chi-square tests applied to assess differences in residue concentrations, bacterial loads, and resistance profiles. Antibiotic residues in all samples remained within permissible thresholds; for instance, streptomycin residues averaged 147.09 ± 14.2 µg/L, well below the EU/Armenian limit of 200 µg/L. Nevertheless, multidrug-resistant bacteria were detected. Five distinct resistance profiles were identified among non-pathogenic bacteria, and up to two phenotypically different resistant isolates were recovered from some samples. These findings indicate that the current implementation of HACCP alone may be insufficient to fully prevent AR dissemination, underscoring the need for stricter regulatory oversight and complementary interventions, including molecular-level surveillance.